The cascudos of the genus Hypostomus Lacépède (Ostariophysi: Loricariidae) from the rio Iguaçu basin - Julio César Garavello; Heraldo Antônio Britski; Claudio Henrique Zawadzki (Neotropical Ichthyology)
We reviewed several large collections of the genus Hypostomus from the rio Iguaçu basin summing up to 793 specimens mainly from the Laboratório de Ictiologia do Departamento de Ecologia e Biologia Evolutiva from Universidade Federal de São Carlos, from fish collection of Núcleo de Pesquisas em Limnologia, Ictiologia e Aquicultura da Universidade Estadual de Maringá, and from the Museu de História Natural do Capão da Imbuia. Hypostomus albopunctatus, H. commersoni, H. derbyi, and H. myersi are redescribed and Hypostomus nigropunctatus is described as a new species. A practical key for identification of Hypostomus species from the rio Iguaçu is also provided.